Implementation and Security Analysis of LAMP Server Using UFW Firewall on VirtualBox Based Ubuntu Server - Heru Setiadi; Nabil Haq; Ridho Wicaksono; Rohiki Mahtum; Abdus Samad (NJCOM: Community Service Journal, 2026)
Web servers using LAMP (Linux, Apache, MySQL, PHP) are a crucial foundation that is highly vulnerable to various cyber threats if not equipped with appropriate protection mechanisms. The purpose of this study is to implement and evaluate the effectiveness of the Uncomplicated Firewall (UFW) firewall on Ubuntu Server operating within a virtual environment with VirtualBox. The methods adopted in this study include the installation and configuration of LAMP services, and the implementation of access control policies on UFW that function to filter incoming and outgoing network traffic. Testing was carried out by checking service connectivity through certain ports and simulating illegal access to assess system reactions. The results of the testing indicate that the implementation of UFW can significantly limit illegal access to server services, while still maintaining the necessary public service access (HTTP/HTTPS) and remote management (SSH). The conclusion of this study underscores that UFW offers a simple and efficient security solution to strengthen web server defenses.